40. Assessment of laser evoked potentials in normal population. Issue 1 (January 2015) - Concon TNFP, E.; Ajena, D.; Tozzi TNFP, M.C.; Monaco, S.; Bertolasi, L.
<x xml:space="preserve">Abstract</x> Laser Evoked Potentials (LEP) represent the most effective method to study the nociceptive pathway, from skin receptors to somatosensory cortex. Unlikely Somatosensory Evoked Potentials and conventional electroneurography, Nd-Yap laser stimulator LEP selectively stimulate small myelinated (Aδ) and unmyelinated (C) fibers. Stimulating the hand's and the feet dorsum bilaterally we studied latency and amplitude of N2-P2 and N1-P1 complexes registered from electrodes placed on median line (Fz, Cz, Pz) and on contralateral temporal lead (T3 or T4) in 50 normal subjects between 23 and 76 ages (mean 40.4), 19 males and 31 females. Mean values of the latency and amplitude of N2-P2 and N1-P1 complexes were considered. Upper limbs: N2 latency is 211 ± 45 ms at right and 211 ± 39 at left, N2-P2 amplitude 45.8 ± 26.1μV at right and 44.5 ± 27.4 at left, N1 latency 174 ± 40 ms at right and 170 ± 32 ms at left. Lower limbs: N2 latency is 250 ± 49 ms at right and 247 ± 57 at left, N2-P2 amplitude 32.2 ± 19.3 μV at right and 32.8 ± 21.0 at left, N1 latency (if it is present) 194 ± 61 ms at left and 200 ± 53 at right. With normative values, we can study nociceptive fibers without invasive techniques, for the valuation of small fibers neuropathy or their integrity in many systemic pathologies.